POTENSI STRUKTUR DAN KEANEKARAGAMAN JENIS VEGETASI PADA OBYEK WISATA ALAM AIR TERJUN BENANG KELAMBU DAN BENANG STOKEL DI KAWASAN HUTAN LINDUNG GUNUNG RINJANI DUSUN PEMOTOH DESA AIK BERIK SEPAGE KECAMATAN BATU KLIANG UTARA KABUPATEN LOMBOK TENGAH - Raden Roro Narwastu Dwi Rita; Yulia Ratnaningsih (SANGKAREANG, 2016)
Gunung Rinjani protected forest area in the hamlet village of Aik Berik Pemotoh Sepage, Batu Kliang North Central Lombok regency are potential natural attractions that water falls benang kelambu and benang Stokel. Of forest areas in the villages Aik Berik has springs that most flows to Central Lombok and West Lombok, two waterfalls has beauty and the beauty and rich flora and fauna. Both these waterfalls make the village Aik Berik as a natural tourist destinations, this waterfall as there are only two in the world, namely in yarn nets and in Japan. The purpose of this study was to determine the potential of the type - the type of vegetation (names of types of vegetation, Values Important Type and index of species diversity in the area of nature Waterfall benang kelambu and Waterfall benangStokel. Types of data collected are primary and secondary data, vegetation data collection used for the analysis of vegetation and species diversity index line method terraced and species diversity index Krebs (1985), for inventory of wildlife using line transect and observation areas along the waterfall. From the analysis conducted vegetation index highest important value for the rate is dadap tree (Erythrina variegate) 57.3%, Lembokek (Ficus septic) 24.78%, Sonokeling (Dalbergia latifolia) 19.31% and Goak (Ficus fistula) 19 07%. To level the pole highest importance value index is Terep (Arthocarpus elasticus) 98.37%, Kepundung (Baccavre racemosa) 59.26%, Brother Bong-bong Lempinyu 17.36% and 15.28%. To saplings highest importance value index is Banana (Musa parasidiaca) 61.22%, Rotan (Daemonorops sp) 31.73%, 17.54% and brother Bongbong Coffee (Caffea sp) 15.18%. And for seedling highest importance value index is Kepundung (Baccavre racemosa) 39.65%, Rotan (Daemonorops sp) 38.92%, 32.47 Lempinyu and Coffee (Caffea sp) 23.53%. Value, biodiversity at the level of the tree (H) 2.902 can be categorized as high, .sedangkan for poles H '2, saplings H' 1,783 and for seedling H '1,895 species diversity is moderate.